Letter from James Curtis Booth to Nanette Bolton, March 22, 1882 - Booth, James Curtis (1882)
James Curtis Booth (1810-1888) writes to Nanette Bolton, a relative, to discuss family matters.
Keywords: Booth, James Curtis, 1810-1888